NiFe-Layered Double Hydroxides/Lead-free Cs2AgBiBr6 Perovskite 2D/2D Heterojunction for Photocatalytic CO2 Conversion - Dong, Zhongliang; Su, Shiwei; Zhang, Zhijie; Jiang, Ying; Xu, Jiayue (Inorganic chemistry, 2023)
Designing of heterojunction photocatalysts with appropriate interfacial contact plays crucial roles in enhancing the interfacial charge transfer/separation. A two-dimensional (2D)/2D face-to-face heterojunction is an ideal option since this architecture with a large contact area can provide abundant reactive centers and promote the interfacial charge transfer/separation between layers. Herein, a novel 2D/2D heterojunction of NiFe-layered double hydroxides (NiFe-LDH)/Cs2AgBiBr6 (CABB) was fabricated by electrostatic self-assembly of NiFe-LDH and CABB nanosheets. This unique 2D/2D architecture endowed NiFe-LDH/CABB with a large contact area and a short charge transport distance, assuring remarkable interfacial charge transfer/separation rates. As a result, the 2D/2D NiFe-LDH/CABB heterojunction exhibited significant improvement in photocatalytic CO2 reduction under visible light than the pristine counterparts. Based on density functional theory calculations and various characterizations, a step scheme charge-transfer mechanism was proposed. This investigation sheds light on the designing and manufacturing of highly efficient 2D/2D heterostructure photocatalysts for artificial photosynthesis.